Tackling gender: girls, football and gender identity construction - Ruth Jeanes (2006)
This thesis examines the construction of young girls' gender identity and the influence participation in football can have on this process. Increasing numbers of girls are now participating in football, a sport which has traditionally been connected with extreme forms of masculinity. The thesis examines the influence participation in football by girls can have on altering dominant and traditional gender assumptions and breaking down the construction of football as a masculine sport. The thesis utilises a feminist post-structural theoretical positioning to enable an understanding of girls' identities as diverse and multiple. The literature reviewed firstly provides an examination of identity theory, girl culture and the influence on global discourses and local mechanisms on girls' gender identity construction. The second phase of the review examines the relevance of sport to the dominant gender order, girls' participation in sport and the potential of sport and football to offer a space in which girls and women can engage in alternative discourses to contest dominant gender values. The methodological approach draws on feminism and the sociology of childhood. A six-month ethnographic study was undertaken in a single school site with thirteen 10 and 11 year old girls. A multi- method, child friendly approach was used to encourage full and direct communication for the girls involved. The study illustrated the diversity and complexity of young girls' gender identities. Global discourses influenced their belief and assumptions surrounding their visual identities, while their friends provided key sources of information about how these should be interpreted in their everyday lives. Football fitted into the girls' feminine gender identities fairly smoothly. Although some of the girls used football to construct `alternative' identities, their participation had little impact on altering either dominant belief surrounding football or reshaping restrictive elements of feminine identities. Despite this the girls' experiences of football were positive, allowing them an open space where contestation of their own negative views about themselves occurs and extend the scripts regarding their own sports abilities and the meaning of football to them. Even when appearing to contest the masculine construction of sport though, the girls' experiences remained highly constrained by gender discourses.